The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.virol.2013.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Expression of non-structural-1A binding protein in lung epithelial cells is modulated by miRNA-548an on exposure to influenza A virus

Abstract: Understanding the host response to influenza A virus infection is essential for developing intervention approaches. We show that infection of human alveolar epithelial cells and human bronchial epithelial cells with influenza A for 3 h resulted in down-regulation of host hsa-miRNA-548an (miRNA-548an) which triggered the overexpression of influenza non-structural-1A binding protein (IVNS1ABP, herein referred to as NS1ABP). Reduced NS1ABP mRNA and NS1ABP protein expression after transfection of miRNA-548an mimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…Subsequently, cells were washed with PBS, and fixed with 4% methanol-free formaldehyde (Polysciences Inc., Warrington, PA). Immunofluorescent staining was done as described earlier (Othumpangat et al, 2013) and stained with rabbit anti-ICAM1 antibody (Millipore, Billerica, MA) for 1 h, followed by Alexa-488 conjugated anti-rabbit secondary antibody and Phalloidin (Life Technologies). The slides were mounted with DAPI-Prolong Gold anti-fade reagent (Life Technologies) and protected with cover slips.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, cells were washed with PBS, and fixed with 4% methanol-free formaldehyde (Polysciences Inc., Warrington, PA). Immunofluorescent staining was done as described earlier (Othumpangat et al, 2013) and stained with rabbit anti-ICAM1 antibody (Millipore, Billerica, MA) for 1 h, followed by Alexa-488 conjugated anti-rabbit secondary antibody and Phalloidin (Life Technologies). The slides were mounted with DAPI-Prolong Gold anti-fade reagent (Life Technologies) and protected with cover slips.…”
Section: Methodsmentioning
confidence: 99%
“…For example, influenza virus infection has been shown to downregulate miR-24 in A549 cells leading to increased furin protease levels and, thus, increased cleavage of the influenza hemagglutinin protein, leading to increased numbers of infectious influenza particles [68] . Also in A549 cells, influenza virus downregulation of miR-548an was shown to lead to increased NS1-binding protein levels and increased RNA stability by decreasing cellular apoptosis [69] . In another study EV71 infection increased miR-141 levels in human rhabdomyosarcoma cells, leading to the downregulation of eukaryotic translation initiation factor 4E protein and thus contributing to the switch from cap-dependent translation of cellular mRNAs to cap-independent translation of virus RNAs [70] .…”
Section: Modulation Of Host Mirna Levels During Viral Infectionsmentioning
confidence: 99%
“…In our previous studies (Othumpangat et al, 2013), we found that infection with influenza virus induced apoptosis. We examined 4 apoptotic pathway genes associated with the intrinsic pathway, and found caspase-9 level was significantly ( p <0.01) increased in HBEpC cells infected with either H1N1 or H3N2 (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Previous studies from our laboratory (Othumpangat et al, 2013) have shown that the levels of influenza non-structural 1A binding protein (IVNS1ABP) changed significantly in A549 cells exposed to influenza virus for 3 h. Examining early stage infection addresses the primary response of the host cells in defending the invading virus. MicroRNA expression profiling using locked nucleic acid (LNA) based miRNA array on A549 cells infected with influenza virus (MOI 3) showed significantly lower expression of several miRNAs in infected cells (Fig.…”
Section: Resultsmentioning
confidence: 99%